Clinical Spectrum of Neurological Complaints in COVID-19: Experiences from a COVID-19 Referral Hospital in Indonesia - Situmeang, Rocksy Fransisca V.; Simanungkalit, Astra Dea; Sutanto, Anyeliria; Pangestu, Aristo (Medicinus, 2021)
Background: The main feature of COVID-19 is symptoms of respiratory system disorder, however, there has been an increase in reports of neurological symptoms that appear in COVID-19 patients. Several previous studies have linked SARS-CoV-2 with nervous system damage. Research studying neurological complaints in  confirmed COVID-19 patients in Indonesia is still lackingAim: To identify neurological, laboratory, and imaging findings in COVID-19 patients with neurological symptoms.Methods: This study was a cross-sectional observational study conducted at Siloam Hospitals Mampang, a COVID-19 referral hospital in South Jakarta. We analyzed medical records of confirmed COVID-19 patients during the period of April - July 2020. The data collected included demographic data, comorbidities, neurological manifestations, laboratory examinations, and neuroimaging.Results: There were 22 confirmed COVID-19 patients with neurological complaints referred to a neurologist. The mean age of patients was 60.4 (SD 15.8) years. The most common neurological complaints were altered mental status (50%), hemiparesis (27.3%), and tremors (22.7%). More than half of the patients (81.8%) had a comorbid condition or past history related to neurological symptoms. Laboratory examination results showed increased NLR (neutrophil-lymphocyte ratio) (50%), anemia (45.5%), and leukocytosis (40.1%). The most common neuroimaging feature was infarct (50%) in the brain CT scan.Conclusion: The neurological complaints in COVID-19 patients are mostly associated with exacerbation of pre-existing comorbidities as a result of the severe inflammatory process triggered by COVID-19. Further research is needed to establish the mechanism of nervous system dysfunction in COVID-19.